IMPROVING SOCIAL SCIENCE LEARNING OUTCOMES BY USING THE LEARNING MODEL THINK PAIR SHARE VIIB CLASS STUDENTS SMP 4 TOLITOLI - Arisa Darwis (Universitas Madako Tolitoli, 2020)
The background of the problem in this study is the students of SMP 4 Tolitoli, the lack of students who actively participate in the learning process and tend to be passive. This study generally aims to improve the social learning outcomes of class VIIB students of SMP 4 Tolitoli. This type of research is a classroom action research. The subjects of this study were 20 students of class VIIB SMP 4 Tolitoli. The data analysis technique used is quantitative by giving value to student learning outcomes. The indicators for the success of the action are marked by a minimum of 70% of the total number of students in the good and very good categories (≥70% of the observed results). The results showed that the application of the Think Pair Share learning model in class VIIB SMP 4 Tolitoli could improve social learning outcomes. Student learning outcomes were carried out in action in the first cycle in the form of learning activities using the Think Pair Share learning model. In the first cycle, it was 45%, students were in the Less category, 40% were in the sufficient category, and 15% were in the good category. Student learning outcomes have increased in cycle II, this can be proven by the results obtained, namely 5% get enough categories, 75% get good categories, and 20% get very good categories, this means they have achieved the specified completeness.Keywords: Think Pair Share learning model, social learning outcomes